The Impact of The Criminal Offence of Extortion Device: A Law Enforcement Perspective - Iga Intani Descatherine Muslimah; Saptaning Ruju Paminto; Aji Mulyana; Kuswandi (Indonesian Journal of Law and Justice, 2025)
The rapid development of information technology presents new challenges in the field of law, especially related to cyber crime. One of the most alarming forms is the attack of extortion devices (ransomware), against Indonesia's National Data Centre (PDN). This research aims to analyse the implementation of Law No. 17/2011 on State Intelligence in overcoming the crime of blackmail devices, the impact on national security, and the relevance of Law No. 1/2024 on Electronic Information and Transactions. The method used is normative juridical with an analytical approach to legislation. The results showed that ransomware fulfils the elements of a criminal offence as stipulated in the Criminal Code and the Electronic Information and Transaction Law. In addition, the role of intelligence agencies is very important in early detection and handling of cyber threats. This research confirms the importance of synergy between intelligence agencies and legal reform in dealing with evolving cyber threats